An intelligent device for mask disposal and clean mask offering - JIAN, QIWEI; Li, Jiaying; Wu, Jiahong; Zhang, Lei; Zhang, Chunyan (IJRDO - Journal of Mechanical And Civil Engineering, 2022)
Based on investigations of current mask treatment situations and requirements, an intelligent device is designed for disposing of used masks and offering clean masks. The multi-function intelligent device is small in size and simple in operation. Contactless delivery and automatic disposal of used masks can be achieved. Ultraviolet disinfection and automatic packaging of used masks will be carried out subsequently. The requirement of providing clean masks can be also addressed in this device. The application of this intelligent device can be promoted in communities with a large stream of people, such as schools, hospitals and shopping malls.